2017
DOI: 10.3390/en10030275
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Performance Analysis of a Biogas-Fuelled Micro-Gas Turbine with a Bottoming Organic Rankine Cycle for Sewage Sludge and Food Waste Treatment Plants

Abstract: Abstract:In the Republic of Korea, efficient biogas-fuelled power systems are needed to use the excess biogas that is currently burned due to a lack of suitable power technology. We examined the performance of a biogas-fuelled micro-gas turbine (MGT) system and a bottoming organic Rankine cycle (ORC). The MGT provides robust operation with low-grade biogas, and the exhaust can be used for heating the biodigester. Similarly, the bottoming ORC generates additional power output with the exhaust gas. We selected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Kim et al 53 used biogas to run a micro gas turbine (MGT), which is combined with an organic Rankine cycle (ORC) as shown in Figure 4. The biogas of this system was provided by sewage sludge and food waste.…”
Section: Biogas‐fueled Electrical Power Productionmentioning
confidence: 99%
“…Kim et al 53 used biogas to run a micro gas turbine (MGT), which is combined with an organic Rankine cycle (ORC) as shown in Figure 4. The biogas of this system was provided by sewage sludge and food waste.…”
Section: Biogas‐fueled Electrical Power Productionmentioning
confidence: 99%
“…The electrical efficiency of micro gas turbines was more stable, while the electrical efficiency decreased only 0.4% for a 60% methane concentration compared to typical natural gas [13]. A study on thermodynamic assessment of integrated biogas-based micro-power generation system showed that gas turbine cycle is more efficient in terms of utilization of recovered exergy than organic Rankine cycle [14]. The air pollutant emission and maintenance requirements of micro gas turbines would be lower than these from internal combustion engines [15].…”
Section: Introductionmentioning
confidence: 97%
“…Interest in biogas as a potential fuel has been recently turned out to be increasing for decentralized heat and power generation as there is a great potential in Subsaharan Africa for biogas production with overly 600 million people without access to any electricity grids. The application of biogas in organic Rankine cycle (ORC) with high capacities turbine combustor was previously revealed possible from both economic [12] and practical point of view [13]. Biogas showed great net present value (NPV) as a sustainable affordable fuel in a wide range of power demands in turbines [14].…”
Section: Introductionmentioning
confidence: 99%